Green Synthesis of Cu-BDC Nanosheets for Methylene Blue Degradation - Nanda Saridewi; Agustino Zulys; Ridla Bakri (Bulletin of Chemical Reaction Engineering & Catalysis, 2025)
Metal Organic Frameworks (MOFs) with two-dimensional (2D) nanosheet morphology possess unique surface characteristics, making them highly favourable for photocatalytic applications. This study synthesised Cu²⁺-based MOF nanosheets using a modified three-layer method. This approach is relatively simple, energy-efficient, and qualifies as a green synthesis method. The MOFs were prepared from copper(II) nitrate trihydrate (Cu(NO₃)₂·3H₂O) as the metal precursor and 1,4-benzenedicarboxylic acid (H₂BDC) as the organic linker, aiming to evaluate their photocatalytic activity for methylene blue degradation. The resulting Cu-BDC nanosheets displayed characteristic FTIR absorption bands at 1501 and 1547 cm⁻¹ corresponding to symmetric and asymmetric C=O stretching, 1394 cm⁻¹ for C–O stretching, and peaks at 751 and 569 cm⁻¹ associated with Cu–O vibrations. The XRD analysis revealed four sharp peaks at 2θ values of 8.2°, 10.2°, 16.1°, and 34.1°, indicating good crystallinity with a calculated crystallite size of 22.03 nm, and the bandgap energy is 3.89 eV. Cu-BDC nanosheets exhibit a thin sheet morphology with elemental compositions of carbon 73.08%, oxygen 11.19%, and copper 15.73%. Cu-BDC nanosheets exhibit optimal degradation activity at pH 13, with an optimal catalyst dose of 5 mg and an initial dye concentration of 20 ppm, achieving a degradation capacity of 98.62 mg/g after 120 minutes of reaction. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).